WALLABY Pilot Survey: H i in the Host Galaxy of a Fast Radio Burst - Glowacki, Marcin; Lee-Waddell, Karen; Deller, A.T.; Deg, N.; Gordon, A.C.; Grundy, J.A.; Marnoch, L.; Shen, A.X.; Ryder, S.D.; Shannon, R.M.; Wong, O.I.; Dénes, H.; et al. (2023)
We report on the commensal ASKAP detection of a fast radio burst (FRB), FRB 20211127I, and the detection of neutral hydrogen (H i) emission in the FRB host galaxy, WALLABY J131913-185018 (hereafter W13-18). This collaboration between the CRAFT and WALLABY survey teams marks the fifth, and most distant, FRB host galaxy detected in H i, not including the Milky Way. We find that W13-18 has an H i mass of M HI = 6.5 × 109 M ⊙, an H i-to-stellar mass ratio of 2.17, and coincides with a continuum radio source of flux density at 1.4 GHz of 1.3 mJy. The H i global spectrum of W13-18 appears to be asymmetric, albeit the H i observation has a low signal-to-noise ratio (S/N), and the galaxy itself appears modestly undisturbed. These properties are compared to the early literature of H i emission detected in other FRB hosts to date, where either the H i global spectra were strongly asymmetric, or there were clearly disrupted H i intensity map distributions. W13-18 lacks a sufficient S/N to determine whether it is significantly less asymmetric in its H i distribution than previous examples of FRB host galaxies. However, there are no strong signs of a major interaction in the optical image of the host galaxy that would stimulate a burst of star formation and hence the production of putative FRB progenitors related to massive stars and their compact remnants.